Upaya Perlindungan Hukum Bagi Pemilik Merek dari Perdagangan Kosmetik Share-in Jar - Firdausy, Sheril; Mahanani, Anajeng Esri Edhi (SIGn Jurnal Hukum, 2021)
This study aims to analyze and understand the legal protection towards the mark owner from the share-in jar cosmetic trade and the legal consequences for business actors who do share-in jar cosmetic trade. The type of legal research used in this study is a normative juridical legal research method. The data collection in this study was conducted through a literature study from the laws and regulations, journals, research results, and books. The data analysis used in this research is the descriptive analysis method. The results of the study show that the legal protection towards the mark owner from the share-in jar cosmetic trade can be carried out through preventive and repressive legal protection efforts. Legal protection efforts are preventively carried out by registering the mark to get legal protection as a legal mark owner. Repressive legal protection efforts for trademarks can be done by litigation dispute resolution and non-litigation dispute resolution. The legal consequences for business actors who do share-in jar cosmetic trade are compensate for damages and/or ceasing all acts related to mark use. Therefore, it is recommended to the mark owner to provide cosmetics with trial or sample sizes. In this case, so that consumers try first about their compatibility with these cosmetics. On the other hand, business actors doing share-in cosmetic jar trade must make a license agreement with the mark owner. Furthermore, the government needs to include criteria for violations of right on mark in laws and regulations. This is purpose to increase legal protection towards the mark owner from the share-in jar cosmetic trade in the future.